Developing Interactive Digital Comic Media for Teaching Speaking Skills in Elementary School - Rini Syamsiah Nur Alifah; Meiliana Nurfitriani; Anggia Suci Pratiwi (PANYONARA: Journal of English Education, 2026)
Mastering English at an early stage is considered crucial in equipping younger generations to face international competition. Among the four essential language abilities, speaking is regarded as the most fundamental and therefore requires consistent and structured development. Nevertheless, the oral proficiency of Indonesian elementary school learners remains relatively low, creating a demand for more engaging and innovative teaching strategies. This research was conducted to design interactive learning resources in the form of a digital comic, intended to support fifth-grade pupils in studying English as a second language (ESL). The study adopted a research and development (R&D) framework to construct instructional media that are tangible, visually oriented, and aligned with the developmental characteristics of children in their early learning stages. The validation process yielded a mean score of 3.7 out of 4, which fell into the â€œvery goodâ€ category. Moreover, effectiveness for the concern and the result was investigated by comparing pre-test and post-test differences, yielding an N-Gain score of 0.87, which is classified as â€œhigh.â€ These results prove that the interactive digital comic not only is user-friendly but is also effective in developing students' speaking skills. The implications extend beyond classroom practice, where teachers can utilize the media as an engaging instructional resource. Additionally, curriculum developers may consider the findings as input in designing syllabi that integrate interactive media, while educational media producers can adopt the principles demonstrated in this study to create child-friendly learning content that supports language acquisition.